2012
DOI: 10.19030/jabr.v28i6.7340
|View full text |Cite
|
Sign up to set email alerts
|

Giving Patterns By Religious And Non-Religions People

Abstract: Using the Oaxaca-Blinder (1994) decomposition method to compare the giving levels of money and time of those who claim to attend religious services on a regular basis with those who do not, we find that on average religious people donate more money and time than non-religious people; although a large portion of the average difference is unexplained. We propose that these differences arise from a culture of giving in which religious people are embedded. It may be that individuals who are religious are more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(8 reference statements)
0
6
0
1
Order By: Relevance
“…Ranganathan and Henley (2008) found that religiosity has an impact on the individual's attitudes toward helping others and their attitudes toward the charitable organization, which in turn affects the individual's intentions to donate. This is echoed with research by Simmons and Emanuele (2012), who found that religious people are more likely to donate time and money when compared to those who were not religious. With this in mind, the question on whether religion could play a significant role in determining the characteristics of charitable donations in the context of Australia arises.…”
Section: Psychographic Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ranganathan and Henley (2008) found that religiosity has an impact on the individual's attitudes toward helping others and their attitudes toward the charitable organization, which in turn affects the individual's intentions to donate. This is echoed with research by Simmons and Emanuele (2012), who found that religious people are more likely to donate time and money when compared to those who were not religious. With this in mind, the question on whether religion could play a significant role in determining the characteristics of charitable donations in the context of Australia arises.…”
Section: Psychographic Factorsmentioning
confidence: 95%
“…Literature identifies religion as an important issue on the characteristics of charitable donations (e.g., van Beest & Wiliams, 2011;Ranganathan & Henley, 2008;Simmons & Emanuele, 2012). Schlegelmilch et al (1997) proposed that it is very important to take into consideration that religious donation to mosques and churches and other religious organizations is one of the fundamental aspects or criteria in the teachings of religion.…”
Section: Psychographic Factorsmentioning
confidence: 99%
“…Scholars have explained that religious belief is a key psychographic characteristic to help determine the differences between donors and non-donors (Ranganathan and Henley, 2008;Simmons and Emanuele, 2012). It is conceptualised that individuals that are perceived to be more religious are more likely to donate (Ranganathan and Henley, 2008).…”
Section: Religious Beliefsmentioning
confidence: 99%
“…According to Mokhlis (2009), religion is a cultural factor that is one of the most universal and influential social institutions that has an impact on the behaviour, attitudes and values of an individual and the society as a whole. Scholars have explained that religious belief is a key psychographic characteristic to help determine the differences between donors and non-donors (Ranganathan and Henley, 2008;Simmons and Emanuele, 2012). It is conceptualised that individuals that are perceived to be more religious are more likely to donate (Ranganathan and Henley, 2008).…”
Section: Religious Beliefsmentioning
confidence: 99%
“…Dini ilgilenim, bireylerin gündelik hayatında birçok konuda tercihlerini etkilemektedir. Çalışma özelinde, kar amacı gütmeyen kuruluşlarla ilgili yapılan çalışmalarda, araştırmacıların bağış yapan ile yapmayanlar arasındaki farklılıkları belirlemede dini ilgilenimin belirleyici bir rol oynadığını açıklamışlardır (Ranganathan ve Henley, 2008;Simmons ve Emanuele, 2012). Daha dindar olan bireylerin daha fazla bağışta bulundukları gözlemlenmiştir (Ranganathan ve Henley, 2008).…”
Section: Dini İlgilenimunclassified